Corporate sustainability reporting in Japanese multinational enterprises: a threat to local legitimacy or an opportunity lost for corporate sustainability practices?. Issue 1 (11th January 2021) - Ike, Masayoshi; Donovan, Jerome Denis; Topple, Cheree; Masli, Eryadi Kordi
Abstract : Purpose: This paper aims to investigate whether Japanese manufacturing multinational enterprises (MNEs) maintain local legitimacy in their host countries through adequate informing of local stakeholders with targeted corporate sustainability (CS) reporting. Design/methodology/approach: The paper first identified specific CS activities that were considered important in four Association of Southeast Asian Nations host countries, through semi-structured interviews with 58 participants of 16 Japanese manufacturing MNEs. The degree of establishment of local legitimacy was then measured through the number of references made to these CS activities and other activities specific to the respective host countries in the CS reports of the MNEs across a five-year period. Findings: The majority of MNEs in the sample were under-reporting items of specific interest to localhost country stakeholders potentially undermining the MNEs' image. There were found to be differences on the topics published in CS reports compared to those mentioned in the interviews indicating potential issues with regard to internal communication between the subsidiary and headquarters offices. Originality/value: A novel approach is taken to investigate the degree of local legitimacy established by MNEs through comparing the contents of interviews held at subsidiaries with their respective CS reports. This paper highlights the importance of considering MNE subsidiaries when addressing Target 12.6 of the Sustainable Development Goal 12: responsible consumption and production.